1993
DOI: 10.1007/bf00197772
|View full text |Cite
|
Sign up to set email alerts
|

ABR frequency tuning curves in dolphins

Abstract: Tone-tone masking was used to determine auditory brain-stem response tuning curves in dolphins (Tursiops truncatus) in a simultaneous-masking paradigm. The Q10 of the curves was as large as 16-19 in the frequency range 64-128 kHz. In the range 45-16 kHz, Q10 decreased proportionally to the frequency with the bandwidth of the curves being constant, about 3.5-4 kHz at the 10-dB level. Tuning curves below 45 kHz are supposed to reflect broad spectral bandwidth of the probe's effective part which is no longer than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 28 publications
1
16
1
Order By: Relevance
“…The active electrode was placed in the dorsal part of the head, at the midline, 6 8 cm behind the blowhole, above the water surface. This site was shown to be the best for ABR recording, and the used electrode position made it possible to compare recorded responses with those described earlier using the same recording technique (Popov and Supin 1990;Supin et al 1993). The reference electrode was in the back near the dorsal fin, also above the water surface.…”
Section: Evoked Response Recordingmentioning
confidence: 99%
See 3 more Smart Citations
“…The active electrode was placed in the dorsal part of the head, at the midline, 6 8 cm behind the blowhole, above the water surface. This site was shown to be the best for ABR recording, and the used electrode position made it possible to compare recorded responses with those described earlier using the same recording technique (Popov and Supin 1990;Supin et al 1993). The reference electrode was in the back near the dorsal fin, also above the water surface.…”
Section: Evoked Response Recordingmentioning
confidence: 99%
“…Our previous work (Supin et al 1993) has demonstrated that this method is effective to investigate frequency tuning in dolphins. The ABR can be recorded easily from the dolphin's head surface, without any surgical procedure and anesthesia.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We investigated temporal processing using auditory evoked potentials (AEPs). AEPs measure neural activity from the auditory nerve and brainstem in response to acoustic stimuli, and they are a common tool for studying auditory processing in humans and other animals (Brittan-Powell et al, 2010a,b;Gall et al, 2013;Hall, 2007;Henry and Lucas, 2008;Higgs et al, 2002;Katbamna et al, 1992;Kenyon et al, 1998;Ladich and Fay, 2013;Popov and Supin, 1990;Supin et al, 1993). We used two well-established AEP techniques that have been used previously to investigate temporal processing: the auditory steady-state response (ASSR) evoked by AM tones and the auditory brainstem response (ABR) evoked by paired acoustic clicks (Burkard and Deegan, 1984;Dolphin and Mountain, 1992;Gall et al, 2013;Henry and Lucas, 2008;Mann et al, 2005;Purcell et al, 2004;Wysocki and Ladich, 2005).…”
Section: Introductionmentioning
confidence: 99%